Anda di halaman 1dari 3

# EXAMPLES An Initial-Value Problem

Solve y'
+
y = f(t), y(O) = 5, where f(t) = { 0
3 cost,
0 ::5 t < 7T,
t ;::::: 7T.

SOLUTION The function! can be written asf(t) = 3 cos toU(t- 7T) and so by linearity, the
results of Example 8, and the usual partial fractions, we have

+
!i{y'} !i{y} = 3!{costoU(t- 7T)}

+ s
sY(s)- y(O) Y(s) = -3 2 + e-1Ts
s 1

+ 3s
(s l)Y(s) = 5 - --2 + e-1T
s 1

(17)

Now proceeding as we did in Example 7, it follows from (15) with a = 7T that the inverses
of the terms in the bracket are

1
e-1Ts } = e- <t- 1T)oU(t- 7T),
1
e-1Ts } = sin(t- 7r)oU(t- 7T),

and !-1
s
+
1
e-1Ts } = cos(t- 7T) oU(t- 7T).

## Thus the inverse of (17) is

3 +
2 y(t) = 5e-1 l e-(t -1T!oU(t - 7T) - l sin(t- 7r)oU(t- 7T) _ l cos(t- 7r)oU(t- 7T)
2 2 2
1

-1 = 5e-t
+
% [e-(t-1T) +
sint
+
cost ] oU(t- 7T) +-trigonometric identities

2n 3n

## FIGURE 4.3.7 Graph of function (18) in

= { 5e -1,
5e-1
+
e-<t- 1T)
+
sint
+
cost,
0 ::5 t < 7T
t ;::::: 7T.
(18)
Example9
With the aid of a graphing utility we get the graph of (18), shown in FIGURE 4.3.7.

D Beams In Section 3.9 we saw that the static deflectiony(x) of a uniform beam of length L
carrying load w(x) per unit length is found from the linear fourth-order differential equation
d4y
EI dx4 = w(x), (19)

where Eis Young's modulus of elasticity and I is a moment of inertia of a cross section of the beam.
The Laplace transform is particularly useful when w(x) is piecewise defined, but in order to use the
transform, we must tacitly assume that y(x) and w(x) are defined on (0, oo) rather than on (0, L).
Note, too, that the next example is a boundary-value problem rather than an initial-value problem.

## EXAMPLE 10 A Boundary-Value Problem

w(x) A beam of length L is embedded at both ends as shown in FIGURE 4.3.8. Find the deflection of
the beam when the load is given by

wall
w(x) =
{( w 1- x ,
o L
) 0 < x ::5 U2

x 0, U2 < x < L,
where w0 is a constant.

SOLUTION Recall that, since the beam is embedded at both ends, the boundary conditions
FIGURE 4.3.8 Embedded beam with a are y(O) 0, y'(O)
= 0, y(L) 0, y'(L)
= 0. Now by (10) we can express w(x) in terms of
= =

## 228 CHAPTER 4 The Laplace Transform

w(x) = wo 1 - ( i) x - wo ( i ) ( - )
1 - x au x

= - x+ x - ( ) ( )]. au x -

## Transforming (19) with respect t o th e variable x gives

2w0 L/2 1 1 -
El(s4Y(s) - s3y(O) - s2y'(O) - sy"(O) - y"'(O)) = - - - - + - e un.
L s s 2 s2
[ ]
2w0 L/2 1 1
or s4Y(s) - sy"(O) - y"'(O) = - - - - + - e -un. .
EIL s s2 s2
[ ]
If we let CJ = y"(O) and c2 = y"'(O), then

CJ c 2w0 L/2 1 1 -
Y(s) =- + -2 + - s - - + - e un. '
s3 s4 EIL s s6 s6
[ - J
and consequently

y(x) =
-J 2!
2!

s3
{ } { }C
+ 2
3!
-J 3!
s4

+
EIL 4!
[ { }
2w0 L/2 -J 4!

s5
{ } _ _!_ -J 5!
5! s6
+
_!_ -J 5! -un
5!
{
s6
e }]

Applying the conditions y(L) = 0 and y' (L ) = 0 to the last result yields a system of equations
for CJ and c2:

L2 L3 49w0 L4
c-+c-+
J 2 6 =O --

2 1920/

L2 85w0 L3
CJL + C2 z + =0.
%OE/

## Solving, we find CJ = 23woL21960EI and c2 = -9woLf40EI. Thus the deflection is

y(x) =
23woL2
1920E/
x2 -
3woL
SOE/
x3 +
Wo
60EIL
[ 5L
TX
( L 5
4 - x5 + x - 2 au x - 2) ( L)] . -

## Cfll Translation on the s--axis

In Problems 1-20, find either F(s) orf(t), as indicated.
1. {te10t} 2. {te-6t}

## 5. {t(et +e2t )2} 6. {e2t (t - 1)2 }

{et sin 3t} {e-21 cos 4t}
7.

## 9. {(1 - et +3e-4t ) cos 5t}

8.
15. J { 2
s
s + 4s + 5
}
4.3 Translation Theorems 229
L
E0 R

In Problems 21-30, use the Laplace transform to solve the given FIGURE 4.3.9 Circuit in Problem 35
initial-value problem.
21. y'+ 4y = e-41, y(O) = 2
36. Use the Laplace transform to find the charge q(t) in an
RC-series when q(O) = 0 and E(t) =E0e-k1, k > 0. Consider
22. y' - y = 1+ t e1, y(O) = 0 two cases: k * l/RC and k= l/RC.
23. y"+ 2y'+ y = 0, y(O) = 1, y'(O) = 1

24. y" - 4y'+ 4y = t3 e21, y(O) = 0, y'(O) = 0 Cffj Translation on the t-axis
25. y" - 6y'+ 9y = t, y(O) = 0, y'(O) = 1 In Problems 37-48, find either F(s) orf(t), as indicated.
26. y" - 4y'+ 4y = t3, y(O) = 1, y'(O) = 0
37. !e{(t- l)oU(t-1)} 38. !{e2-1 oU(t- 2)}
27. y" - 6y'+ 13y = 0, y(O) = 0, y'(O) = -3 39. !e{toU(t- 2)} 40. !{(3t+ l)oU(t-1)}
28. 2y" + 20y'+ 5ly = 0, y(O) = 2, y'(O) = 0

## 29. y" - y' = e1 cos t, y(O) = 0, y'(O) = 0

41.

43.
e 2
!- 1 -
{ s}
!{cos 2t oU(t- 1T)}
-
42.

44. !- 1
{ 1 e-2')2 }
!{ sintoU(t - ?T/2)}
( +

{ } { }
30. y" - 2y'+ 5y = 1+ t, y(O) = 0, y'(0) = 4
s3 s+2
- -n
se
In Problems 31 and 32, use the Laplace transform and 45. !-l e
!- 1 --

{ s2 } { s2 e-24s }
46.
the procedure outlined in Example 10 to solve the given +1 +
boundary-value problem. -
e
1 1
47. ! 48. !
31. y"+ 2y'+ y = 0, y'(O) = 2, y(l) = 2 s(s + 1) s2(s - 1)
32. y"+ Sy'+ 20y = 0, y(O) = 0, y'('rr) = 0
33. A 4-lb weight stretches a spring 2 ft. The weight is released
In Problems 49-54, match the given graph with one of the given
from rest 18 in above the equilibrium position, and the result functions in (a)-(f ). The graph off(t) is given in FIGURE 4.3.10.
ing motion takes place in a medium offering a damping force
numerically equal to times the instantaneous velocity. Use
the Laplace transform to find the equation of motion x(t).
34. Recall that the differential equation for the instantaneous
charge q(t) on the capacitor in an LRC-series circuit is a b

## d2q dq 1 FIGURE 4.3.10 Graph for Problems 49-54

L- + R- + -q = E(t). (20)
dt2 dt c (a) f(t)-f(t) oU(t- a)
(b) f(t- b) oU(t- b)
See Section 3.8. Use the Laplace transform to find q(t) when (c) f(t) oU(t- a)
L=1 h,R=200, C=0.005 f,E(t)=150 V, t> 0, q(O)=0, (d) f(t)-f(t) oU(t- b)
and i(O) = 0. What is the current i(t)? (e) f(t) oU(t- a)-f(t) oU(t- b)
35. Consider the battery of constant voltageE0that chargesthe capac (f) f(t- a) oU(t- a)-f(t- a) oU(t- b)
itor shown in FIGURE 4.3.9. Divide equation (20) by L and define 49. 50.
2,\ = RIL and w2 = l/LC. Use the Laplace transform to show f(t)

(\
f(t)
that the solution q(t) of q"+ 2,\q'+ w2 q = E0/L, subject to
q(O) = 0, i(O) = 0, is I I
I I
I

[
a b a b

E0c 1 - - w2t FIGURE 4.3.11 Graph for FIGURE 4.3.12 Graph for

+
,\2
A - w21 . )] A> w
Problem49 Problem50

[ ]
_

w2 51. f(t)
q(t) = E0c 1 - e-At(l + A t) . A =w
I I

E0c [ {
I I
I I

## 1- e-.1. cos w2 - A.2t a

)]
b

+
A sin w2 - A2t . ,\. < w. FIGURE 4.3.13 Graph for
w2 _
,\2 Problem51